Have Public Finances in the OECD Area Been Sustainable? - Ferraz Ricardo (Economics and Business)
The aim of this article is to test, from an empirical standpoint, the existence of sustainable public finances in the Organisation for Economic Co-operation and Development (OECD) area as a whole, over the most recent period of the world economy, 1973-2016. The research methods include not only standard stationarity tests, but also tests, which allow for a structural break. The relevant results of this research are a stationary public budget balance expressed as a percentage of GDP and a debt to GDP ratio that is stationary in first differences. According to the literature, this means that a “necessary and sufficient” condition is fulfilled for proving the existence of a strong sustainability. We hope this research can make a valuable contribution to the debate regarding public finances in the world economy. To obtain other relevant conclusions, additional tests will need to be performed in the future in order to assess which members are contributing to the fiscal sustainability of the OECD aggregate.